Open Data Repository DataverseUA: Practical experience - Svistunov, Sergiy; Svirin, Pavlo (State Scientific and Technical Library of Ukraine, 2025)
In 2022, Ukraine adopted the National Open Science Plan (approved by the Decree of the Cabinet of Ministers of Ukraine on October 8, 2022, No. 892-р), which defined the tasks for the implementation of open science principles, ensuring open access to scientific results and scientific and technical information, as well as research infrastructure, publications, and scientific data. The National Academy of Sciences of Ukraine (NAS of Ukraine) has actively joined the implementation of the tasks of the National Open Science Plan and, by its resolution “On the participation of the NAS of Ukraine in the implementation of the European principles of open science” (approved by the Presidium of the NAS of Ukraine on February, 2022, No. 327, has defined the priority work for its implementation. The talk presents the results of the implementation of the target scientific and technical project of the NAS of Ukraine “Development and implementation of open science infrastructure in the NAS of Ukraine (OPENS)” for 2023-2024, in part of the creation of the Open Data Repository of the NAS of Ukraine and the experience of supporting its operation.